Association between non-alcoholic fatty liver disease and arterial stiffness in the non-obese, non-hypertensive, and non-diabetic young and middle-aged Chinese population - Yu, Xin-yan; Zhao, Yi; Song, Xiao-xiao; Song, Zhen-ya (Journal of Zhejiang University. B. Science, 2014)
Background and objective Non-alcoholic fatty liver disease (NAFLD) is associated with arterial stiffness in the general population. Age, obesity, hypertension, and diabetics are risk factors for arterial stiffness. In this study, we aimed to investigate the association between NAFLD and arterial stiffness as measured by brachial-ankle pulse wave velocity (baPWV) in the non-obese, non-hypertensive, and non-diabetic young and middle-aged Chinese population. Methods A cross-sectional study with 1296 non-obese, non-hypertensive, and non-diabetic young and middle-aged (20–65 years) subjects undergoing routine medical check-ups in the International Health Care Center of the Second Affiliated Hospital of School of Medicine of Zhejiang University was carried out. Fatty liver was diagnosed by ultrasonography, and baPWV was measured using an automatic waveform analyzer. The subjects were classified into two groups according to the presence of NAFLD, and divided into a further two groups according to their baPWV. Results The overall incidence of NAFLD was 19.0%, and NAFLD patients had a significantly higher level of baPWV than the controls ((1321±158) cm/s vs. (1244±154) cm/s; P <0.001). The incidence of NAFLD was clearly higher in the increased baPWV group than in the normal baPWV group (29.3% vs. 16.9%; P <0.001), and the incidence increased in line with the increase of baPWV quartiles in the normal range as well as with the severity of arterial stiffness (both P for trend <0.001). Multiple linear logistic regression analysis showed that the presence of NAFLD was positively and independently associated with baPWV. Conclusions Our results suggest that the presence of NAFLD is associated with arterial stiffness as measured by baPWV in the non-obese, non-hypertensive, and non-diabetic young and middle-aged Chinese population.